Procedimiento alternativo para premedicación y anestesia de primates (no humanos). Uso de ketamina y halotano - Arcila Quiceno, Victor Hernan; Reyes, Hector; Reyes, Jorge; Sanchez, Favio (Spei Domus, 2005)
Every time is more frequent the presence of wild fauna in veterinary centers. Lack of studies about medical aproach and the poor availability of research reports in this species, imply the necesity to propose empiric protocols, including anesthetics. A primate (Cebus albifrons) with hind limb fracture, was exposed to surgical management of anesthetics including acerpomacine maleate, morphine hydrochlorate and ketamina hydrochlorate as well as halotane at maintenance doses according to literature recommendations to other species. No undesirable effects were observed during surgical or post-surgical procedure.